Hubungan Status Ekonomi Keluarga Dengan Kejadian Kekerasan Pada Anak (Child Abuse) Di Komunitas Anak Jalanan Kota Mojokerto - Iis Fatimawati (MEDICA MAJAPAHIT, 2014)
The lives of street children and involvement in economic activity has been realized or not cause problems for them. Because not only education but also sacrificed his soul development. Those who had to give up his childhood to portray themselves as adults compete with the rigors of life in the big city, with spending time on the streets just to add a bit of relief to the people and their parents. The purpose of this study to the economic status of the family relationship with the incidence of child abuse (child abuse) in the community of street children in Mojokerto. Analytic study design is correlational cross-sectional approach. This study economic status variables as independent variables and the incidence of child abuse as the dependent variable. This research entire population of street children in Mojokerto as many as 51 children. Samples were taken by purposive sampling technique by 30 respondents. Data were collected by questionnaires and processed in editing, coding, scoring and tabulating then analized with the chi square test. The results showed that of the 17 respondents belonging to high socioeconomic status, there were 7 respondents who experienced child abuse and 10 respondents who did not experience child abuse. The results of Chi-square test showed the results Ï = 0.016 and Î± = 0.05, then Ï <Î± so that H0 is rejected and H1diterima means there is a relationship between family economic status to the incidence of child abuse. Parents who do not have jobs will result in financial pressure, poverty, debt burden, making it less able to control anger, is likely to do violence on children. Working parents protracted, go early and go home late afternoon, leaving little time and energy to perform domestic tasks and child care. So that children become neglected and forgotten because of fatigue. For families expected to improve understanding of the impact of child abuse in order to prevent the occurrence of acts of child abuse.